2022
DOI: 10.1136/archdischild-2021-323303
|View full text |Cite
|
Sign up to set email alerts
|

Children living with disabilities are neglected in severe malnutrition protocols: a guideline review

Abstract: PurposeChildren living with disabilities are at high risk of malnutrition but have long been marginalised in malnutrition treatment programmes and research. The 2013 WHO guidelines for severe acute malnutrition (SAM) mention disability but do not contain specific details for treatment or support. This study assesses inclusion of children living with disabilities in national and international SAM guidelines.MethodsNational and international SAM guidelines available in English, French, Spanish or Portuguese were… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 14 publications
0
24
0
Order By: Relevance
“…Disadvantaged groups should be considered when identifying the target audience of a proposed guideline 55 …”
Section: Resultsmentioning
confidence: 99%
“…Disadvantaged groups should be considered when identifying the target audience of a proposed guideline 55 …”
Section: Resultsmentioning
confidence: 99%
“…Specific interventions should include capacity strengthening and addressing misperceptions and biases among health workers and revising guidelines and care protocols related to nutrition and health to include appropriate guidance and support for children with feeding difficulties. Given high rates of wasting and early mortality due to malnutrition among children with disabilities, an opportunity exists to provide guidance on children with disabilities in the forthcoming revision of wasting guidelines [44]. However, the Global Action Plan on Wasting contains only very brief mention of children with disabilities [60].…”
Section: Discussionmentioning
confidence: 99%
“…One respondent added that health workers frequently do not recognize or address sensory-related feeding problems, such as selective eating or oral hypersensitivity (Interview with a SLT). A review found that better evidence is needed on identifying and managing children with disabilities in malnutrition programs [44], which was supported by respondents (see Box 1). Another report found that "the nutrition sector needs to provide program staff with better guidance and training on how to manage children with neurodisabilities.…”
Section: Targeted Services For Managing Feeding Difficultiesmentioning
confidence: 98%
See 2 more Smart Citations